Improved insulin sensitivity following a short-term whole body vibration intervention - John Babraj; Adam Hawkey (Al Ameen Medical College, 2017)
Background and Objective: Despite being recommended for reducing the risk of type 2 diabetes (T2D) the majority of the population do not partake in the advised amount of regular exercise. While high intensity type training has been shown to produce improvements in insulin sensitivity its uptake in high risk populations has been questioned. Contrastingly, whole body vibration training (WBVT) is reported to benefit a range of outcomes in a variety of populations. Limited data exists regarding this training modality on insulin sensitivity. Current study assessed the effect of WBVT on oral glucose tolerance response. Method: Following institutional ethics approval, five young healthy sedentary individuals undertook oral glucose tolerance test (OGTT) prior to and on completion of 5-week progressive WBVT. Result: There were no changes in fasting plasma glucose concentrations before and after the 6 weeks of WBVT. Both pre- and post-training OGTT revealed no significant changes in plasma glucose concentrations over time. There was a 9% reduction in plasma glucose area under the curve (AUC) post training. The Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) decreased by 21% and Cederholm index of insulin sensitivity was increased by 18% following WBVT. Conclusion: Results suggest WBVT is associated with improved insulin sensitivity and could produce clinically relevant effects on fat metabolism in sedentary young people. Large-scale studies are now necessary to assess the effectiveness of WBVT in diabetic populations.